Analysis of activation and shutdown contact dose rate for EAST neutral beam port. (December 2017) - Chen, Yuqing; Wang, Ji; Zhong, Guoqiang; Li, Jun; Wang, Jinfang; Xie, Yahong; Wu, Bin; Hu, Chundong
Abstract: For the safe operation and maintenance of neutral beam injector (NBI), specific activity and shutdown contact dose rate of the sample material SS316 are estimated around the experimental advanced superconducting tokamak (EAST) neutral beam port. Firstly, the neutron emission intensity is calculated by TRANSP code while the neutral beam is co-injected to EAST. Secondly, the neutron activation and shutdown contact dose rates for the neutral beam sample materials SS316 are derived by the Monte Carlo code MCNP and the inventory code FISPACT-2007. The simulations indicate that the primary radioactive nuclides of SS316 are 58 Co and 54 Mn. The peak contact dose rate is 8.52 × 10 −6  Sv/h after EAST shutdown one second. That is under the International Thermonuclear Experimental Reactor (ITER) design values 1 × 10 −5  Sv/h. Highlights: The neutron intensity of EAST plasma centre is increased to 1.0 × 10 14  n/s when the neutral beam with energy 58 keV is injected into EAST plasma with line-averaged density 3.0 × 10 13 /cm 3 . The beam-target reaction is the main contribution to the total neutron emission under the EAST current operating condition. The shutdown contact dose rate at the sample material is 8.52 × 10 −6  Sv/h after shutdown one second. That implies the personal can access to NBI system for maintenance and repair after EAST shutdown.